2018
DOI: 10.1002/anzf.1331
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related Issues in Couple Therapists’ Internal Voices and Interactional Practices

Abstract: The study demonstrates how motherhood gender-related discourse is intertwined with the ways in which the systemic techniques and systemic thinking are realised in the session. This research explores the consequences of gender-related discourse commonly co-constructed by participants in couple therapy and not recognised or challenged by the therapist. Video-recorded data from a couple therapy session containing unrecognised genderrelated discourse were subjected to conversation analysis (CA). The interview (Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
0
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
3
0
0
3
Order By: Relevance
“…(2017), who found that women can better understand their environment and its interconnectivity, relevant to developing systems thinking. This result is also supported by Vico and Rebollo (2019), Janusz et al . (2018) and Otálora (2017), who linked women's sense of motherhood and social role to the systems thinking sub-competency.…”
Section: Theoretical Frameworksupporting
confidence: 83%
See 1 more Smart Citation
“…(2017), who found that women can better understand their environment and its interconnectivity, relevant to developing systems thinking. This result is also supported by Vico and Rebollo (2019), Janusz et al . (2018) and Otálora (2017), who linked women's sense of motherhood and social role to the systems thinking sub-competency.…”
Section: Theoretical Frameworksupporting
confidence: 83%
“…Specifically, as shown in Table 2, we found significant data showing that women perceive their mastery level positively in the sub-competency of systems thinking, especially in its values and attitudes (items 8 and 9). These results contrast with the study by Khammarnia et al (2017) but are in line with Monterroso et al (2017) and Janusz et al (2018). According to Nagahi et al (2019), women solve complex problems by recognizing their individuality and role as part of a group.…”
Section: Discussionsupporting
confidence: 68%
“…Różne cele badawcze mogą wymagać różnych metod, jednak z całą pewnością interesującą opcją jest wykorzystanie nagrań i transkrypcji sesji terapeutycznych, co pozwala na bardzo szczegółowe analizowanie również zmian zachodzących w narracjach osoby badanej w pewnej perspektywie czasowej (por. Janusz, Józefik, Peräkylä, 2018). Oczywiste jest jednak, że w wielu przypadkach dużo lepiej może sprawdzić się pojedynczy wywiad ukierunkowujący narrację badanego na konkretny, interesujący temat lub pozwalający badać wywołane bodźcami narracyjnymi zjawisko (por.…”
Section: Cele I Rezultaty Badań Nad Zaburzeniami Osobowości Z Wykorzystaniem Wywoływania I Analizy Autonarracjiunclassified
“…Doświadczenia terapeuty, jego skojarzenia czy wspomnienia mogą być źródłem konstruktywnych interwencji, dzięki lepszemu rozumieniu podobnych doświadczeń, jak i powodem niebezpiecznych zniekształceń z powodu emocjonalnego zaangażowania terapeuty we własne odniesienia. Rezultaty badania przeprowadzonego przez Józefik i Janusz [13] dotyczącego problematyki genderowej pokazały, że psychoterapeuci podczas terapii rodzinnej, terapii par i terapii indywidualnej w dużym stopniu odwołują się do swoich doświadczeń. Przytoczone badania dotyczyły jedynie deklaracji psychoterapeutów, niemniej jednak ukazały również ważność pytania o rzeczywiste odnoszenie się do wydarzeń biograficznych psychoterapeutów.…”
Section: Wstępunclassified
“…czas teraźniejszy i przeszły w wypowiedzi terapeuty) pozwalające określić, które osobiste wspomnienia czy też osobiste przeżycia terapeuty pojawiły się na sesji terapeutycznej, a które w trakcie wywiadu z terapeutą. W związku z tym można stwierdzić, iż IPR jest narzędziem do eksplorowania wewnętrznych głosów terapeuty wzbudzonych zjawiskami zachodzącymi w pracy terapeutycznej i możliwymi do wypowiedzenia/zreflektowania w trakcie wywiadu [13]. W terapii rodzin/par istnieje znacznie więcej niż w terapii indywidualnej czynników potencjalnie przywołujących osobiste głosy terapeuty.…”
Section: Wnioskiunclassified